Prenatal stress alters the behavior and dendritic morphology of the medial orbitofrontal cortex in mouse offspring during lactation. Issue 7 (30th May 2013) - Gutiérrez‐Rojas, Cristian; Pascual, Rodrigo; Bustamante, Carlos
Abstract: Several preclinical and clinical studies have shown that prenatal stress alters neuronal dendritic development in the prefrontal cortex, together with behavioral disturbances (anxiety). Nevertheless, neither whether these alterations are present during the lactation period, nor whether such findings may reflect the onset of anxiety disorders observed in childhood and adulthood has been studied. The central aim of the present study was to determine the effects of prenatal stress on the neuronal development and behavior of mice offspring during lactation (postnatal days 14 and 21). We studied 24 CF‐1 male mice, grouped as follows: (i) control P14 ( n = 6), (ii) stressed P14 ( n = 6), (iii) control P21 ( n = 6) and (iv) stressed P21 ( n = 6). On the corresponding days, animals were evaluated with the open field test and sacrificed. Their brains were then stained in Golgi‐Cox solution for 30 days. The morphological analysis dealt with the study of 96 pyramidal neurons. The results showed, first, that prenatal stress resulted in a significant (i) decrease in the apical dendritic length of pyramidal neurons in the orbitofrontal cortex at postnatal day 14, (ii) increase in the apical dendritic length of pyramidal neurons in the orbitofrontal cortex at postnatal day 21, and (iii) reduction in exploratory behavior at postnatal day 14 and 21.